AI-Infused Smart Cities: Transforming Kosovo's Urban Landscape for Sustainable Growth - Hasani, Engjulla (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics